Financial Management Behavior analysis: The Role of Financial Attitudes and Consumptive Behavior as Mediating - Mardiyani; Dwiputri Khusnul Chotimah; Rafi Murtadha Astaghfirullah (Indonesian Journal of Business Analytics, 2025)
This research has the objective to explore the relationship between financial literacy, financial attitude, as well as consumptive behavior. The conduct of data analysis was with the use of SEM-PLS with the SmartPLS3 application and implemented a quantitative approach with a causal associative research design. The findings revealed that financial literacy significantly influences financial attitude, consumptive behavior, as well as financial management behavior. On top of direct effects, financial attitude and consumptive behavior also serve as mediators that strengthen the relationship between financial literacy with financial management behavior. This research’s implications suggest that digital and interactive financial education strategies must be optimized to help millennials develop prudent financial attitudes, planned consumption patterns, and more responsible financial management.